Implementation of Dance Self-Development Activities at SMPN 2 Kandis, Kandis District, Siak Regency - Umrintha, Dinna; Ayuthia Mayang Sari (Universitas Negeri Padang, 2024)
This study aims to find and describe the planning of dance self-development activities and the implementation of dance self-development activities in SMP Negeri 2 Kandis, Kandis District, Siak Regency. This type of research is qualitative research with a descriptive method. The instruments of this study are the researchers themselves and are assisted by supporting instruments such as stationery, flash drives and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps of analyzing data are data reduction, data presentation and data inference. The results of the study show that dance self-development activities at SMPN 2 Kandis consist of planning, implementation and appreciation of coaches. The planning of the dance self-development activity program at SMPN 2 Kandis has been well coordinated and appropriate according to the plan made by the coach, starting from the schedule, time, in accordance with the purpose of the program. The implementation of dance self-development activities at SMPN 2 Kandis has gone well and the coaches are trying their best to make the students who participate in the activity practice well according to the schedule and place. The appreciation of the coach by displaying the students' dance works is one of the motivations for students to continue practicing so that they are more confident in displaying the results of exercises that have been done well.